Oviposition acceptance and larval development of Chilo partellus stemborers in drought‐stressed wild and cultivated grasses of East Africa. Issue 3 (15th April 2014) - Chidawanyika, Frank; Midega, Charles A.O.; Bruce, Toby J.A.; Duncan, Frances; Pickett, John A.; Khan, Zeyaur R.
Abstract Maternal host choices during oviposition by herbivorous insects determine the fitness of their offspring and may be influenced by environmental changes that can alter host‐plant quality. This is of particular relevance to 'push‐pull' cropping systems where host preferences are exploited to manage insect pest populations. We tested how drought stress in maize and companion plants that are used in these systems affect oviposition preference, larval feeding, and development of the spotted stemborer, Chilo partellus Swinhoe (Lepidoptera: Crambidae). Five host species were tested (all Poaceae): maize (Zea mays L.), Napier grass (Pennisetum purpureum Schumach), signal grass [Brachiaria brizantha (A. Rich) Stapf], Brachiaria cv. 'Mulato', and molasses grass [Melinis minutiflora (Beauv.)]. Under drought stress, maize experienced as much oviposition as control unstressed maize in choice and no‐choice experiments. Similarly, larval leaf damage was not significantly different in drought‐stressed vs. unstressed maize. In contrast, oviposition occurred less on drought‐stressed than on unstressed Napier and signal grass. Oviposition acceptance and leaf damage remained low in both drought‐stressed and unstressed molasses grass and Mulato. Larval survival and development remained high in drought‐stressed maize, but not in Napier, signal, and molasses grass and Mulato, where survival and development were low in both drought‐stressed and unstressed plants. Our results indicate that herbivore responses to drought‐stressed plants depend on the plant species and that drought stress can change host preference and acceptance rankings. In particular, trap‐crops such as Napier grass may not divert oviposition from the main maize crop under drought stress conditions.